The Arctic Fish Haemoglobins - A. Riccio; D. Giordano; G. Mangiapia; G. di Prisco; C. Verde; VERGARA, ALESSANDRO; PADUANO, LUIGI; MAZZARELLA, LELIO (2010)
The urgency to investigate evolutionary adaptations at high latitudes is increasing considerably, especially in the Arctic. Similar to Antarctic notothenioids, Arctic fish endemic to high latitudes have adapted to thermally stable waters and therefore their physiological systems are finely tuned to the narrow temperature range they are experienced to. Given the short evolutionary time at polar temperatures, Arctic fish may provide valuable information on the effects of environmental temperature on specific physiological and biochemical traits (1, 2). Fish hemoglobins have been extensively studied, not only for their structural and functional properties, but also because they offer the possibility to investigate functional differentiation and molecular adaptations in species living in a large variety of environmental conditions. In addition, Arctic fish hemoglobins appear to be good models for studying sickling disorders and hemoglobin-polymerisation processes. In this study we report the structural and functional characterisation of the single hemoglobin of Lycodes reticulatus (family Zoarcidae) living on the sea floor near the coasts of northern Europe and North America. The hemoglobin shows a low Bohr effect and no Root effect;it tends to form high-molecular mass polymers at physiological pH and low temperature (5°C), as shown by gel-filtration chromatography and dynamic light scattering. The elucidation of the primary structure has allowed to establish correlation between functional behaviour (no Root effect) and structural properties (polymerisation). The large number of cysteyl residues in the α and β subunits, typical of hemoglobins of many Arctic species, e.g. several gadids, brings about the capability to produce polymers. Also the hemoglobins of Arctogadus glacialis, Boreogadus saida and Gadus morhua (2), similar to L. reticulatus hemoglobin, contain additional His and Cys residues in their primary structure which potentially account for polymerisation (3). References 1 Verde, C., Carratore, V., Riccio, ...